Between Asian and America: geopolitics, globalization, and international migration - Wei Li; Wan Yu (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2014)
In this paper we will briefly review recent histories of Asian civilizations, with a focus on the accelerated international division of labor and economic growth across Asia over the last half century. We also look at the relationship with US immigration admission policies toward Asian immigrants and their consequences. We then address the recent shift from a one-way brain drain (from developing countries–in this case Asia, to developed countries–the United States) to a model of networked brain circulation among developing and developed nations. Finally we connect immigration policies and their consequences with the US’s Asia policies.